The Influence Of Facilities And Services On Passenger Satisfaction At PT. Sempati Star In Medan - Rangkuti, Dian Natama Sandi; Sahputra, Ngatno; Firah, Al (Universitas Dharmawangsa Medan, 2024)
The purpose of this research is to determine the influence of facilities and services on passenger satisfaction at PT. Sempati Star in Medan. This research was carried out at PT. Sempati Star in Medan which is located at Jl. Pondok Kelapa Dormitory No.19, Sei Sikambing C, Medan Helvetia, Medan City, North Sumatra 20122, Indonesia. Based on the calculation results of the influence of facilities on passenger satisfaction, it was obtained tcount (3.544) > ttable (1.681), with a significance level of 0.00 < 0.05. The value 3.544 is greater than 1.681 indicating that tcount is greater than ttable. From these results it can be concluded that Ha is accepted (Ho is rejected). This shows that there is a significant influence of facilities on consumer satisfaction. Based on the partial calculation results of the influence of service on passenger satisfaction, tcount (4.813) > ttable (1.681), with a significance level of 05 < 0.05. The value 4.813 is greater than 1.681 indicating that tcount is greater than ttable. From these results it can be concluded that Had was accepted (Ho was rejected). This shows that there is a significant influence of service on consumer satisfaction. Based on the table above, it can be seen that the Fcount value is 42.468 with a significance level of 0.00, while the Ftable is 3.220 with a significance level of 0.05. Thus, Fcount> Ftable is 42.468 > 3.220. The value 42.468 is greater than 3.220, indicating that tcount is greater than ttable, meaning that Ho is rejected so it can be concluded that there is a simultaneous influence of facilities and services on passenger satisfaction at PT. Sempati Star in Medan. From the calculation results it can be seen that the coefficient of determination obtained is 0.669. This means that 66.9% of the variation in the passenger satisfaction variable (Y) is determined by the two independent variables, namely Facilities (X1) and Service (X2). Meanwhile, the remaining 33.1% was influenced by other variables not studied.